Urgensi Pembatasan Kekuasaan Presiden Dalam Pengangkatan Wakil Menteri Pasca Reformasi - Ahmad Ilham Wibowo; Karina Maharani Alkhusna (Fakultas Hukum Universitas Islam Indonesia, 2021)
Law Number 39 of 2008 gives the president authority to appoint a Deputy Minister. However, the appointment of the Deputy Minister, both in terms of regulation and practice, did not restrict the power of the President as mandated by the 1945 Constitution after the reform. There are 2 problem formulations in this research: first, what are the dynamics of the post-reformation arrangements for the appointment of Deputy Minister for President? Second, what is the urgency of limiting the power of the President in appointing the Deputy Minister in post-reformation era? This is a normative research using statutory, conceptual, case and historical approaches. The results conclude that first, the arrangement of the presidential authority to appoint Deputy Minister has undergone various changes which resulted in a wide space for the President to appoint and determine the number of Deputy Minister. Second, there is an urgency to limit the power of the President to appoint Deputy Minister because the regulations in the State Ministry Law still has gaps in the domination of the President’s political interests, not based on the existence of certain expertise for workloads that require special handling and not in line with the effectiveness and efficiency of the state ministries. Limitation of power can be carried out by providing clear terms and indicators and involving the DPR’s considerations in the appointment of the Deputy Minister